rewrtie the middle term as the sum of 2 terms and then fator completely.
12w^2+19w+4
I can get most of it done with certianty but the end I am afraid is wrong I just need a little help. heres what I am getting
a=12,b=19,c=4
mn=a*c=48 and m+n=b=19
mn=16*3=48 m+n=16+3=19
m=16 and n=3
now here is were I need help
12w^2+19w+4=12w^2+16w+3w+4
=(12w^2+16w)+(3w+4)
=12w(w+8w)+3(w+2)
=(12w+3w)(x+2)
The other probelm that I need help with is the same thing just different numbers,
4z^2-18z^2-10z
I can get through the first part its just the second part giving me trouble.
2007-01-23
20:34:11
·
1 answers
·
asked by
richardsonlover12
1
in
Science & Mathematics
➔ Mathematics